2008
DOI: 10.1590/s1516-14392008000300012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and porosity of dental glass-ceramics hot-pressed at different temperatures

Abstract: The objective of this work was to evaluate biaxial-flexural-strength (σ f ), Vickers hardness (HV), fracture toughness (K Ic ), Young's modulus (E), Poisson's ratio (ν) and porosity (P) of two commercial glass-ceramics, Empress (E1) and Empress 2 (E2), as a function of the hot-pressing temperature. Ten disks were hot-pressed at 1065, 1070, 1075 and 1080 °C for E1; and at 910, 915, 920 and 925 °C for E2. The porosity was measured by an image analyzer software and σ f was determined using the piston-on-three-bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…As a consequence, higher porosity is expected due to the larger amount of space between powder particles following the evaporation of the water, reducing the efficacy of the viscous flow sintering process and resulting in higher porosity levels. 23,25 The porosity level may not be the sole factor affecting the flexural strength of dental ceramics, since a previous study 39 showed that glassceramics with significantly higher porosity (due to processing at higher temperatures) possessed statistically similar flexural strengths to glassceramics with lower porosity levels. It is important to consider that the flexural strength of brittle materials is determined by the flaw population of the tested material, and therefore, the present study showed that the one-step technique produced in a less favorable flaw population resulted in decreased mechanical behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, higher porosity is expected due to the larger amount of space between powder particles following the evaporation of the water, reducing the efficacy of the viscous flow sintering process and resulting in higher porosity levels. 23,25 The porosity level may not be the sole factor affecting the flexural strength of dental ceramics, since a previous study 39 showed that glassceramics with significantly higher porosity (due to processing at higher temperatures) possessed statistically similar flexural strengths to glassceramics with lower porosity levels. It is important to consider that the flexural strength of brittle materials is determined by the flaw population of the tested material, and therefore, the present study showed that the one-step technique produced in a less favorable flaw population resulted in decreased mechanical behavior.…”
Section: Discussionmentioning
confidence: 99%
“…14,38 Open porosity volume was calculated following the determination of the apparent density based on the Archimedes water displacement method. 39 Statistical analysis was conducted using a descriptive approach based in the maximum and minimum values of calculated biaxial flexural strength. The Kolmogorov-Smirnov (KS) test was applied to determine if the Weibull model was an adequate distribution for the experimental data obtained for both groups.…”
Section: Methodsmentioning
confidence: 99%
“…One all-ceramic system is lithium disilicate glass ceramic (Li 2 Si 2 O 5 ), currently used for dental restorations for mainly dental crowns, bridges and veneers because of its excellent mechanical properties, longevity and esthetic characteristics [4][5][6][7][8][9][10][11] . Lithium disilicate glass ceramic has superior optical properties by itself.…”
Section: Introductionmentioning
confidence: 99%
“…The CAD/CAM restorations are better-fitting, more durable and more natural looking (multi-colored and translucent, similar to natural teeth) than previously machined restorations. In addition, CAD/CAM technology has enabled dental clinicians to restore teeth using ceramic material in a single appointment 9 . Meanwhile, hot pressing technology, which most technicians are usually familiar with, demonstrates the ability to produce dental restorations effectively due to a wide variety of pressable and inexpensive ceramics that are available 1,16 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, glass ceramics can be produced by melting glass and converting the substance into a uniform nucleation and growth of fine-grained ceramics by controlled crystallization process, in which the crystalline phases are nucleated and grown in glass via heat treatment [3][4][5]. Lithium disilicate glass ceramic, in particular the Li 2 O-SiO 2 system, is the first material classified as glass ceramic discovered by Stookey as having better mechanical properties over base glass [6].…”
Section: Introductionmentioning
confidence: 99%